Family in recovery - Knowledge Network and Forefront Productions ([S.l.] : Knowledge and Forefront Production [production company] Kuala Lumpur : Visual Resources [distributor], 1991)
This film focuses on a seemingly perfect family that was actually in deep distress. Kathy, 30, and her mother, Helen, each had a long struggle with alcoholism trigged by the tensions caused by an unstable father. All four children in this family had problems of self-esteem and difficulties in relating to one another
Keywords: Alcoholics -- Family relationships; Alcoholics -- Psychology; Alcoholism